The Impact of Competition and Concentration Towards Systemic Risk in Indonesian Banking Industry - Jesslyn Vania; Natasha Eugene Chung (iBuss Management, 2018)
With the advancement of the economy, banks have become very connected to one another. This was one of the causes of why the 2008 crisis in USA was so severe. Because of the contagion effect if one bank collapse, the other banks can start to collapse as well. The purpose of this research is to know whether competition and concentration have any influence towards systemic risk. There are two views in the relationship of competition and concentration toward systemic risk. Competition-stability, meaning competition lower systemic risk and competition-fragility, meaning competition increase systemic risk. Another views are concentration-stability, meaning concentration lower systemic risk and concentration-fragility, meaning concentration increase systemic risk.This research uses the data of 33 commercial banks in Indonesia from 2013-2017 that are listed in Indonesian Stock Exchange (IDX). In analysing the data, multiple regression is used, and the result shows that competition and concentration indeed significantly impacting systemic risk. The control variables that impact systemic risk are size and profitability. While liquidity and asset composition impact to systemic risk are insignificant. Thus, the findings in this research supports competition-fragility view and concentration-stability view. Keyword: Bank competition, bank concentration, systemic risk, financial stability